Curcumin Alleviates oxLDL Induced MMP-9 and EMMPRIN Expression through the Inhibition of NF-κB and MAPK Pathways in Macrophages - Cao, Jiatian; Ye, Bozhi; Lin, Lu; Tian, Lei; Yang, Hongbo; Wang, Changqian; Huang, Weijian; Huang, Zhouqing (Frontiers in Pharmacology, 2017)
Rupture of vulnerable atherosclerotic plaques is the leading cause of acute myocardial infarction (AMI) and unstable angina pectoris (UA). However, it still lacks an effective therapy to stabilize the vulnerable atherosclerotic plaques. Numerous reports have shown that upregulation of MMP-9 (matrix metalloproteinase-9) and EMMPRIN (extracellular matrix metalloproteinase inducer) in macrophages is involved in the progression and development of vulnerable plaques. Here we evaluated the impact of curcumin on the expression of MMP-9 and EMMPRIN in macrophages. Macrophages were pretreated with curcumin or specific inhibitors (p38 MAPK inhibitor, NF-κB p65 inhibitor) for 1 hr, then cells were cultured with oxLDL for indicated time. Real-time PCR and Western blot analysis were used to evaluate the expression of mRNA and proteins. Translocation of NF-κB p65 was detected by using laser confocal microscopy. Here we showed that curcumin attenuated the MMP-9 and EMMPRIN expression in oxLDL stimulated macrophages. Further studies revealed that curcumin inhibited oxLDL induced NF-κB activation and p38 MAPK phosphorylation. These findings illustrated that curcumin can inhibit the expression of EMMPRIN and MMP-9 in oxLDL stimulated macrophages through down regulation of NF-κB and p38 MAPK signaling pathways, which might be the molecular mechanism for the anti-atherosclerotic effect of curcumin.